Dampak Transformasi Mata Pencaharian Terhadap Kondisi Ekonomi dan Sosial Masyarakat (Studi Kasus pada Usaha / Kegiatan Penambangan Mineral Logam Mangan di Wilayah IUP PT Bun Yan Hasanah di Desa Nian Kecamatan Miomafo Tengah Kabupaten Timor Tengah Utara) - Stefanus Frengki Mbawo (Diponegoro University, 2014)
This research was conducted in the area of North Central Timor Government District of Central Miomafo Nian village on 18 November 2013 to 18 May 2014 This study examines the impact of the transformation of the livelihood and economic and social conditions (Case Study On Business / Manganese Mineral Mining Activities Region Iup PT. Bun Yan Hasanah in Nian village Miomafo District of Central North Central Timor). With the aim to determine the impact of the transformation of the livelihood and economic and social conditions, the type of research used is descriptive analytical approach using ex post facto that the data collected after the incident took place. With each study variable, namely (1) changes in the orientation of the public about livelihood, (2) economic conditions, (3) social conditions. The sampling technique was conducted by distributing questionnaires and direct interviews or questionnaires to 20 respondents who are involved actively in mining activities. Data were collected and analyzed by using AHP method. Results and discussion illustrate that the impact on the livelihood transformation of economic conditions showed the highest value of 67% and is followed by changes in the livelihood of 25% and 8% of social conditions. The fact indicates that the level 1 criteria matiks that economic criteria with sub-criteria fulfillment necessities of life ie 27% priority to the welfare of society villagers Nian District of Central Miomafo TTU.